CCAFS – 2017 Annual Reporting: Altmetric Analysis - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In 2017, 818 (or 23.7%) of CCAFS’ 3445 publications in CGSpace received social attention, according to Altmetric. Social attention for CCAFS publications comes primarily from mentions on Twitter (8769), in news articles (775), in blog stories (576), on Facebook (480), and in policy (395), in that order. There are also a few mentions on Google+ (105). Based on these numbers, it appears that Twitter is the primary driver of CCAFS’ Altmetric scores. There were 3 publications (from all years) with Altmetric scores above 500 (see ‘Top-scoring publications’ below), and 25 publications with scores between 101 and 500. Another 21 publications received scores between 51 and 100, and 169 publications had scores between 11 and 50. A further 601 publications received scores of between 1 and 10. Among the 151 publications with mentions from 2017 only, 1 publication received a score of over 500, 3 received scores between 101 and 500, 37 scored between 11 and 50 (with none scoring between 51 and 100), and a further 110 scored between 1 and 10.